2015
DOI: 10.1016/j.neulet.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of morphine tolerance by a compound with NPFF receptor subtype-selective actions

Abstract: Neuropeptide FF (NPFF) modulates opiate actions. It has pro-nociceptive effects, primarily through the NPFF receptor 1 subtype, and anti-nociceptive effects, primarily through the NPFFR2 subtype. AC-263093 is a small l, organic, systemically active molecule that was previously shown to functionally activate NPFFR2, but not NPFFR1. It was hypothesized that AC-263093 would attenuate morphine tolerance. Rats were tested for radiant heat tail-flick latency before and after 5 mg/kg morphine sulfate s.c. They were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…NPFFR1 activation might hypothetically oppose the effects of NPFFR2, dominate NPFF system activity during chronic morphine treatment, and contribute to the development of tolerance to morphine antinociception. This hypothesis could be supported by a recent study (Malin et al., ) that reported AC263093 could reverse morphine tolerance and processes equal binding affinity towards NPFFR1 and NPFFR2 (pKi of 7.0 vs. 6.9, respectively). Interestingly, authors demonstrated AC263093 acts as an NPFFR1 antagonist but NPFFR2 agonist and argued the attenuation of morphine tolerance could be due to either NPFFR1 antagonism or NPFFR2 stimulation (Malin et al., ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…NPFFR1 activation might hypothetically oppose the effects of NPFFR2, dominate NPFF system activity during chronic morphine treatment, and contribute to the development of tolerance to morphine antinociception. This hypothesis could be supported by a recent study (Malin et al., ) that reported AC263093 could reverse morphine tolerance and processes equal binding affinity towards NPFFR1 and NPFFR2 (pKi of 7.0 vs. 6.9, respectively). Interestingly, authors demonstrated AC263093 acts as an NPFFR1 antagonist but NPFFR2 agonist and argued the attenuation of morphine tolerance could be due to either NPFFR1 antagonism or NPFFR2 stimulation (Malin et al., ).…”
Section: Discussionmentioning
confidence: 61%
“…This hypothesis could be supported by a recent study (Malin et al., ) that reported AC263093 could reverse morphine tolerance and processes equal binding affinity towards NPFFR1 and NPFFR2 (pKi of 7.0 vs. 6.9, respectively). Interestingly, authors demonstrated AC263093 acts as an NPFFR1 antagonist but NPFFR2 agonist and argued the attenuation of morphine tolerance could be due to either NPFFR1 antagonism or NPFFR2 stimulation (Malin et al., ). Nevertheless, the mechanisms underlying NPFFR2‐mediated attenuation of morphine tolerance remains unknown.…”
Section: Discussionmentioning
confidence: 61%
“…18 Numerous reports suggest that NPFF exerts antiopioid activities and antagonizes opioid-induced actions including analgesia, tolerance, and reward. [42][43][44] In the present study, we explored the roles of the NPFF agonism in DN-9-induced GI inhibition. Previous studies have demonstrated that NPFF and FMRFamide cause significant contractions in the isolated mouse distal colon and porcine GI smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply the important role of the activation of NPFF receptors in delaying opioid tolerance development to BN‐9. Indeed, previous studies have shown that both an antagonist (RF9) and agonist (AC‐263093) of NPFF receptors decrease morphine tolerance to antinociception (Simonin et al , ; Elhabazi et al , ; Malin et al , ). These conflicting results highlight the complicated relationship between NPFF receptor activation and opioid‐mediated tolerance.…”
Section: Discussionmentioning
confidence: 99%